High-Risk, High-Impact Health Services Research: Developing an Innovation Initiative - Jolie N. Haun; Naomi Tomoyasu; Courtney Paolicelli; Christine Melillo; David Atkins (Journal of Veterans Studies, 2020)
As health systems strive towards innovative solutions to healthcare problems, research programs should be a crucial resource to support the evidence base of innovation. Unfortunately, current research funding processes and infrastructure often produce incremental improvements over an extended timeline. Within the Veterans Health Administration (VHA), the Health Services Research & Development (HSR&D) service used the need for greater innovation to address healthcare problems to examine possible changes in how research is solicited, reviewed, funded, and implemented. Towards this goal, HSR&D has launched the “Innovation Initiative” which includes a new funding mechanism that supports research that has potential for high impact. The aim of this paper is to describe this new funding mechanism for supporting scientific innovation and impact in health services research.